2012
DOI: 10.1063/1.4739408
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics of AlGaN/GaN/AlGaN double heterostructures with high electron mobility

Abstract: The AlGaN/GaN/AlGaN double heterostructure (DH) with high electron mobility of 1862 cm2/Vs at room temperature and 478 cm2/Vs at 573 K high temperature was obtained by a combination of optimization schemes considering scattering mechanisms. First, a composite buffer layer structure, including GaN and AlGaN layer, was used to improve the crystal quality of the AlGaN/GaN/AlGaN DH. Second, interface roughness scattering was reduced by increasing the channel thickness, thus the two-dimensional electron gas mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Up to now, the studies of GaN based devices working at low temperature focus on the following aspects: (1) Enhanced transport properties at low temperature due to the weaker phonon scattering [8], [9]; (2) More excellent DC and RF properties at low temperature [10], [11]; (3) The kink effect associated with impact ionization [12]. Most researches have focused on the characterization of the GaN material and devices at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the studies of GaN based devices working at low temperature focus on the following aspects: (1) Enhanced transport properties at low temperature due to the weaker phonon scattering [8], [9]; (2) More excellent DC and RF properties at low temperature [10], [11]; (3) The kink effect associated with impact ionization [12]. Most researches have focused on the characterization of the GaN material and devices at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the excellent value of 1014 mA mm −1 is even comparable to that of the InAlN DH HEMTs . Actually, a much thicker channel layer is unnecessary because both sheet carrier density and electron mobility will not keep increasing when the channel reaches a critical thickness ; meanwhile, a much thinner channel is also inferior because electrons in it will suffer serious scattering from both interfaces .…”
Section: Resultsmentioning
confidence: 78%
“…In addition, the apparent deterioration of the performance of SH HEMTs at high temperatures has also been observed previously . To improve carrier confinement and alleviate the aforementioned problems, DH (double heterostructure) HEMTs, with a very strong 2DEG (two‐dimensional electron gas) confinement, have been investigated . The superior performances of DH HEMTs including high‐temperature stability , excellent breakdown characteristics , and improved punchthrough characteristics have been presented.…”
Section: Introductionmentioning
confidence: 69%
“…Ozbay and co‐workers have reported that highly resistive GaN layers can be achieved by the growth of a thick HT AlN (0.5 − 1.0 µm) buffer layer on sapphire substrates, however the breakdown voltage of their device was only 60 V. The low breakdown voltage of AlGaN/GaN HEMTs with HT AlN may be due to residual donors in GaN (such as O and Si) incorporated during high‐temperature growth. Because it is necessary to compensate for the residual n‐type conductive GaN buffer to further improve the breakdown voltage of AlGaN/GaN HEMTs on both sapphire substrates and SiC substrates, AlGaN is also widely used to replace GaN buffers to enhance the breakdown . Since, however, AlGaN has poor thermal conductivity, it is probably difficult to achieve both good performances for HEMTs and very high insulating performance of GaN buffers grown on sapphire substrates.…”
Section: Introductionmentioning
confidence: 99%